2017
DOI: 10.14740/jocmr2922e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metformin on Different Non-Diabetes Related Conditions, a Special Focus on Malignant Conditions: Review of Literature

Abstract: Metformin has been proven to be one of the most safe and effective antihyperglycemic agents. Through more than six decades of metformin use, it became the most studied hypoglycemic agent; through these studies, it showed a marvelous non-glycemic related effect. These effects include modulation of different points of cancer timeline, weight reduction, cardiovascular health, thyroid diseases, polycystic ovaries disease and many other medical conditions. The aim of this review was to assess the effect of metformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…In this sense, the use of statin and aspirin are being use in clinical trials (NCT02081638), and in addition antioxidant vitamins, amino acids or other dietary supplements have started to be widespread in the HIV-infected community [18]. Based on our results, metformin and thiazolidinediones, widely used to treat type 2 diabetes, could be potential therapies given that it has been demonstrated that they improve glucose metabolism [69]. Another therapeutic option could be the use of antioxidants, such us vitamin E mentioned before [59].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the use of statin and aspirin are being use in clinical trials (NCT02081638), and in addition antioxidant vitamins, amino acids or other dietary supplements have started to be widespread in the HIV-infected community [18]. Based on our results, metformin and thiazolidinediones, widely used to treat type 2 diabetes, could be potential therapies given that it has been demonstrated that they improve glucose metabolism [69]. Another therapeutic option could be the use of antioxidants, such us vitamin E mentioned before [59].…”
Section: Discussionmentioning
confidence: 99%
“…Both the diet and drugs influence the faecal microbiota [ 4 – 7 ]. Metformin has anti-hyperglycemic and weight-reducing effects, which are beneficial in subjects with obesity [ 8 10 ]. The effects depend in part on the altering of the gut microbiome [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent cohort study found that primary open angle glaucoma patients with type 2 diabetes mellitus (DM), particularly with treated type 2 DM, had significantly slower rates of retinal nerve fibre layer thinning compared to those without DM . Over‐expression of vascular endothelial growth factor in the retina of diabetics or protective effects of metformin on mitochondrial function and retinal ganglion cells may be the underlying mechanism for the protective effect against glaucomatous damage. All these findings may imply that the relatively slower progression of glaucoma may be a potential explanation for the poorer persistence among diabetic patients.…”
Section: Discussionmentioning
confidence: 99%